Mysteries of the bryophyte–tracheophyte transition revealed: enter the eophytes. Issue 3 (4th December 2021) - Tomescu, Alexandru M. F.
Abstract : This article is a Commentary on Edwards et al . (2022a, b), 233 : 1440–1455 and 1456–1465 .